The idea of the Muslim world a global intellectual history - Aydin, Cemil (Harvard University Press, 2017)
As Cemil Aydin explains in this provocative history, it is a misconception to think that the world's 1.5 billion Muslims constitute a single religio-political entity. How did this mistaken belief arise, why is it so widespread, and how can its grip be loosened so that a more fruitful discussion about politics in Muslim societies can begin?